Flame-Retardant and Sustainable Silk Ionotronic Skin for Fire Alarm Systems - Liu, Qiang; Yang, Shuo; Ren, Jing; Ling, Shengjie (ACS materials letters, 2020)
Ionotronic skin (i-skin) has drawn considerable attention, because it can interface with different systems to sense and respond to external stimuli, such as force and temperature. However, safety issues, such as biosecurity, sustainability, and safety in use, are rarely considered in i-skin designs. In this study, a flame-retardant and biosafe i-skin was developed by using silk fibroin and Ca2+ ions as starting materials. The structures, performance, and safety issues of the i-skins were well-balanced. The resultant i-skins not only maintained the advantages of conventional i-skins, such as conductivity, transparency, high stretchability, and self-healing ability, but also featured outstanding flame retardancy and temperature sensibility. With these features, an automated fire alarm system was designed to detect possible fire conditions. Benefiting from their low cost, stretchability, and sustainability, these i-skins are expected to be employed in a range of emerging fields, such as flame-retardant materials, fire alarms, temperature sensors, and human/machine interfaces.